Use of and barriers to access to opioid analgesics: a worldwide, regional, and national study - Berterame, Stefano; Erthal, Juliana; Thomas, Johny; Fellner, Sarah; Vosse, Benjamin; Clare, Philip; Hao, Wei; Johnson, David T; Mohar, Alejandro; Pavadia, Jagjit; Samak, Ahmed Kamal Eldin; Sipp, Werner; et al. (The Lancet (British edition), 2016)
Despite opioid analgesics being essential for pain relief, use has been inadequate in many countries. We aim to provide up-to-date worldwide, regional, and national data for changes in opioid analgesic use, and to analyse the relation of impediments to use of these medicines. We calculated defined daily doses for statistical purposes (S-DDD) per million inhabitants per day of opioid analgesics worldwide and for regions and countries from 2001 to 2013, and we used generalised estimating equation analysis to assess longitudinal change in use. We compared use data against the prevalence of some health disorders needing opioid use. We surveyed 214 countries or territories about impediments to availability of these medicines, and used regression analyses to establish the strength of associations between impediments and use. The S-DDD of opioid analgesic use more than doubled worldwide between 2001–03 and 2011–13, from 1417 S-DDD (95% CI −732 to 3565; totalling about 3·01 billion defined daily doses per annum) to 3027 S-DDD (−1162 to 7215; totalling about 7·35 billion defined daily doses per annum). Substantial increases occurred in North America (16 046 S-DDD [95% CI 4032–28 061] to 31 453 S-DDD [8121–54 785]), western and central Europe (3079 S-DDD [1274–4883] to 9320 S-DDD [3969–14 672]), and Oceania (2275 S-DDD [763–3787] to 9136 S-DDD [2508–15 765]). Countries in other regions have shown no substantial increase in use. Impediments to use included an absence of training and awareness in medical professionals, fear of dependence, restricted financial resources, issues in sourcing, cultural attitudes, fear of diversion, international trade controls, and onerous regulation. Higher number of impediments reported was significantly associated with lower use (unadjusted incidence rate ratio 0·39 [95% CI 0·29–0·52]; p<0·0001), but not when adjusted for gross domestic product and human development index (0·91 [0·73–1·14]; p=0·4271). Use of opioid analgesics has increased, but remains low in Africa, Asia, Central America, the Caribbean, South America, and eastern and southeastern Europe. Identified impediments to use urgently need to be addressed by governments and international agencies. International Narcotics Control Board, UN.